Effect of economic recession on the food purchasing behaviour of people of Karachi - Thaver, Inayat Hussain; Ahmed Sheikh, Farooq; Suri, Hafsa Adnan; Qureshi, Muhammad Abu Bakar Irfan; Ahmed, Atique; Kabani, Areesh Akbar (Journal of the Pakistan Medical Association, 2024)
Economic recessions, extending beyond macro indicators, profoundly impact individual consumers and their food-purchasing behaviour. This study examines how people in Karachi, Pakistan, purchase food and how the recession has affected that activity. Data from 384(100) participants were gathered using the cross-sectional study method in a survey. The sample size was calculated, keeping the confidence level at 95%, with a 5% margin of error. Results highlight significant shifts in purchasing behaviour, with many respondents opting for more economical food choices and reducing spending on non-essential items. Crucially, household size and income level emerged as predictors of these changes. The findings carry implications for legislators and stakeholders, providing insights into food consumption dynamics during economic uncertainty. The study emphasizes the need for targeted policies to navigate the intricate web of individual and familial dietary choices amid economic downturns. Keywords: Economic recession, Food insecurity, Humans, Uncertainty